Nocturnal Southerly Moist Surge Parallel to the Coastline Over the Western Bay of Bengal. Issue 18 (20th September 2022) - Fujinami, Hatsuki; Sato, Tomonori; Kanamori, Hironari; Kato, Masaya
Abstract: The role of the diurnal atmospheric circulation cycle around the eastern Indian subcontinent, leeward of the monsoon westerlies, on the hydroclimate of South Asia remains unknown. Here, we reveal that low‐level moist southerlies are greatly enhanced at night parallel to the coastline over the western Bay of Bengal (BoB), and then flow onto the Gangetic Plain enhancing onshore moisture flux and nocturnal precipitation over the Himalayas and the Meghalaya Plateau. This nocturnal surge is strongly controlled by the diurnal cycle of dynamic and thermodynamic effects around the subcontinent. At night, nocturnal westerly low‐level jets appear over the subcontinent. Strong low‐level southwesterly flow with a low‐level jet structure also appears parallel to the coastline over the western BoB, extending from the west of Sri Lanka. The low‐level westerlies from the subcontinent and the low‐level southwesterlies merge into a single strong southwesterly flow, forming the low‐level moist surge. Plain Language Summary: Nocturnal precipitation is a well‐known phenomenon around the Himalayas and the Meghalaya Plateau in South Asia in summer. Such precipitation is a major supply source for glaciers in the central–eastern Himalayas and the headwaters of major rivers such as the Ganges and the Brahmaputra. In this study, we show that low‐level moist southerlies are greatly enhanced at night parallel to the coastline over the western Bay of Bengal (BoB) and then flow onto the Gangetic Plain, enhancing moisture transport toward land and nocturnal precipitation in South Asia. Here, we refer to the phenomenon as the nocturnal southerly moist surge. This nocturnal surge is strongly affected by the diurnal cycle of the thermal and topographic effects of the Indian subcontinent. At night, a strong low‐level westerly jet appears above the nocturnal stable layer over the Indian subcontinent. Strong low‐level southwesterlies with a low‐level jet structure also appear over the western BoB, extending from the strait between the southernmost tip of the Indian subcontinent and Sri Lanka. The low‐level westerlies flowing from the subcontinent and the southwesterlies merge into a single strong southwesterly flow, forming the low‐level moist surge over the western BoB. Key Points: Nocturnal low‐level southerly moist surge occurs parallel to the western Bay of Bengal coastline and flows over the Gangetic Plain The surge consists of strong low‐level westerlies from the Indian subcontinent and southwesterlies extending from the west of Sri Lanka Dynamic and thermodynamic effects of the Indian subcontinent likely play an important role in forming the nocturnal surge